Current status and perspective of tumor immunotherapy for head and neck squamous cell carcinoma - Yu, Chenhang; Li, Qiang; Zhang, Yu; Wen, Zhi-Fa; Dong, Heng; Mou, Yongbin (Frontiers in Cell and Developmental Biology, 2022)
Head and neck squamous cell carcinoma (HNSCC) have a high incidence and mortality rate and investigating the pathogenesis and potential therapeutic strategies of HNSCC is required for further progress. Immunotherapy is a considerable therapeutic strategy for HNSCC due to its potential to produce a broad and long-lasting antitumor response. However, immune escape, which involves mechanisms including dyregulation of cytokines, perturbation of immune checkpoint, and recruitment of inhibitory cell populations, limit the efficacy of immunotherapy. Currently, multiple immunotherapy strategies for HNSCC have been exploited, including immune checkpoint inhibitors, costimulatory agonists, antigenic vaccines, oncolytic virus therapy, adoptive T-cell transfer (ACT) and epidermal growth factor receptor (EGFR)-targeted therapy. Each of these strategies has unique advantages, and the appropriate application of these immunotherapies in HNSCC treatment has significant value for patients. Therefore, this review comprehensively summarizes the mechanisms of immune escape and the characteristics of different immunotherapy strategies in HNSCC to provide a foundation and consideration for the clinical treatment of HNSCC.